(NrASSKAZY (B/ s (N~ASTX (B4s - (N{OLOM(B-(NaLEJHEMs ((NmOSKWA(B: s (NgOSUDARSTWENNOE IZDATELXSTWO HUDOVESTWENNOJ LITERATURY(B, s, 1960)
(Nw ^ETWERTYJ TOM WO[LI RASSKAZY IZ KNIG (B"(NnEUNYWA@]IE(B", "(NkASRILOWKA(B" (NI (B"(NnOWAQ kASRILOWKA(B".s
rus
Keywords: (NrASSKAZY(B, (NPOWESTIs